(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the issues of the selection procedure for applicants to military educational institutions. Undoubtedly, an important component of the processes of organizing military education is the selective selection of both physically and mentally mature personnel. As a result of conditions created for the development of a well-rounded generation, which is considered a priority component of the state youth policy in the conditions of Uzbekistan, the interest of young people who want to get an education in the military field is higher than ever.